KEPUASAN WISATAWAN DALAM PENGGUNAAN E-COMMERCE AGODA DALAM PEMESANAN HOTEL - Suci Sandi Wachyuni; Kadek Wiweka (Journal of Tourism Destination and Attraction, 2020)
The industrial revolution that entered the 4.0 phase encouraged the industry to innovate, where one of the developing industries was e-commerce. As part of the OTA (tourism industry), e-commerce, or especially Agoda offers not only products but also services. However, at the moment, Agoda can be said to be left behind if we look at the ranking of the top brand awards, 2019. Therefore this research intends to examine the satisfaction of tourists (consumers) in using Agoda for booking a hotel. The approach used in this research is descriptive quantitative, where primary data is collected through a questionnaire with indicators of customer satisfaction (Repurchase, Word of Mouth, Brand Image, Product Quality, Price, Service Quality, and Emotional Factor). The scale used is Likert (1-5), and the sampling technique used is probability sampling, which is simple random sampling with a total of 100 respondents. The secondary data is taken from Agoda's website, books, literature, and previous research. The study was conducted during June-July 2019. This study found that the average tourist was quite satisfied - satisfied with Agoda's services in booking hotels. However, to maintain its existence, Agoda needs to make efforts to attract tourists, especially in improving the Agoda brand image. Also, the cooperation partners, which are hotels, will have high confidence in marketing their hotels through Agoda. Furthermore, in terms of the marketing segment, Agoda is very firmly attached to the millennial generation in meeting accommodation needs. However, it is interesting to investigate further the purpose of booking this accommodation, whether for travel needs or other vacation concepts, like one of the popular concepts nowadays, "staycation". This research is expected to provide information about service conditions and customer satisfaction using Agoda. So the results of this study can be useful not only for Agoda companies but also for other OTAs who offer similar products or services. Keywords: kepuasan wisatawan, e-commerce, pemesanan hotel, online travel agent (OTA)